Chimeric Flap for Reconstruction of Severe Traumatic Injuries of the Hand (a Case Report) - Atmodiwirjo, Parintosa; Harihadi, Eko (Lingkar Studi Bedah Plastik Foundation, 2012)
Background: Injuries of the hand, including loss of digits, are devastating events. Patients often require multiple operative procedures, with prolonged recovery periods. The challenge for the reconstructive surgeon is to minimize the number of operations, shorten the recovery period, and restore the function and aesthetic appearance of the hand. When faced with a difficult reconstruction, the expense, morbidity of the donor site, and operative time must be taken into consideration. The chimeric composite flaps is combination of microanastomoses consist of two flaps or tissue, each with an isolated pedicle and a single vascular source. Patients and Methods: We reported a case of 32-year-old man presenting with skin defect of hand, flexor and extensor tendon expose due to traffic accident after passed critical event and debridement we did chimeric flaps consist of free radial forearm flap and free dorsalis pedis flap based on radial pedicle system and dorsalis pedis pedicle system. Result: 2 weeks postoperative, flap were vital with satisfactory functional and aesthetic outcome and almost all of graft was take as well as all of donor site graft.Summary: In selected cases, the chimeric flap is a good option for the reconstruction of extensive, composite, and three-dimensional defects.